Comparison of plantar load when running on treadmill and on cement and grass overground surfaces - Hong, Y.; Wang, L.; Zhou, J. -H. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The objective of this study was to compare plantar loads during running on a treadmill and on concrete and grass surfaces. Sixteen experienced heel-to-toe runners participated in the study. Plantar loads were collected using a Novel Pedar insole sensor system during running at 3.8 m/s. Compared with running on the two other surfaces, treadmill running showed a lower magnitude of maximum plantar pressure and maximum plantar force for the total foot, maximum plantar pressure for the two toe regions, maximum plantar force for the medial forefoot and the two toe regions, and longer absolute contact time at the two toe regions (p<0.05). The results suggest that treadmill running may be useful in early rehabilitation programs. Patients with injuries in their lower extremities may benefit from the reduction in plantar loads.